Prostaglandin production by human gingival fibroblasts inhibited by triclosan in the presence of cetylpyridinium chloride - Kim, Y. J.; Rossa, C.; Kirkwood, K. L. (Amer Acad Periodontology, 2005)
Background: the effect of triclosan plus the cationic detergent cetylpyridinium chloride (CPC) was evaluated for prostaglandin inhibition in human gingival fibroblasts. Since triclosan has previously been shown to inhibit proinflammatory cytokine induced prostaglandin E-2 (PGE(2)) production, we wanted to determine if triclosan, in the presence of CPC, could enhance these effects.Methods: Initial studies determined that both triclosan and CPC were cytotoxic to human gingival fibroblasts in concentrations exceeding 1.0 mu g/ml for either agent longer than 24 hours in a tissue culture. Therefore, subsequent studies measuring prostaglandin biosynthesis and cyclooxygenase (COX)-1 and COX-2 mRNA expression were performed in concentrations and times that did not significantly affect cell viability.Results: PGE2 biosynthesis was dose dependently inhibited by both triclosan and triclosan and CPC when challenged by tumor necrosis factor (TNF)-alpha or interleukin (IL)-1 beta. At pharmacologically relevant concentrations, triclosan and CPC inhibited ILAP-induced PGE(2) production to a greater extent than triclosan alone (P = 0.02). Moreover, enhanced COX-2 mRNA repression was observed with triclosan and CPC in comparison to triclosan alone in IL-1 beta and TNF-alpha stimulated cells. No effect on COX-I gene expression was observed. Further analysis of cell signaling mechanisms of triclosan and CPC indicates that nuclear factor-kappa B (NF-kappa B) and not p38 mitogen-activated protein kinase (MAPK) signaling may be impaired in the presence of triclosan and CPC.Conclusion: This study indicates that triclosan and CPC are more effective at inhibiting PGE(2) at the level of COX-2 gene regulation, and this combination may offer a potentially better anti -inflammatory agent in the treatment of inflammatory lesions in the oral cavity.
Keywords: cetylpyridinium chloride; COX-2; fibroblasts; PGE(2); triclosan